Good Intentions: Paving the Road to Hell - Nyren, Nathan (My University, 2008)
From 1932 until 1972, the Public Health Service, with the assistance of several other prominent groups and individuals, carried out a study of untreated syphilis in Macon County, Alabama. The study contained roughly 600 African American males, which met a predetermined set of criteria. Some of them were syphilitic while others served as controls for the study. Initially they were given a negligible amount of treatment, at the request of the county board of health, but the latter part of the study withheld treatment completely. By 1946, syphilis could easily be treated and cured with penicillin, but these men were still barred from treatment. The study did not conclude until 1972 due to a large public expression of disapproval. This paper will cover the effects of untreated syphilis, the logistics and implementation of the study, and then will conclude with how the study ties into the Eugenics movement and how it is still effects research and ideas today.
Keywords: Human experimentation in medicine--Alabama--Macon County; Syphilis--Research--Alabama--Macon County; Tuskegee Syphilis Study; African American men--Diseases--Alabama--Macon County; Eugenics--History